Population and antenatal-based HIV prevalence estimates in a high contracepting female population in rural South Africa - Rice, Brian D.; Bätzing-Feigenbaum, Jörg; Hosegood, Victoria; Tanser, Frank; Bärnighausen, Till; Herbst, Abraham Jacobus; Newell, Marie-Louise (BMC public health, 2007)
To present and compare population-based and antenatal-care (ANC) sentinel surveillance HIV prevalence estimates among women in a rural South African population where both provision of ANC services and family planning is prevalent and fertility is declining. With a need, in such settings, to understand how to appropriately adjust ANC sentinel surveillance estimates to represent HIV prevalence in general populations, and with evidence of possible biases inherent to both surveillance systems, we explore differences between the two systems. There is particular emphasis on unrepresentative selection of ANC clinics and unrepresentative testing in the population.
Gesehen am 22.06.2017